Kewirausahaan Mahasiswa PAI melalui Warung Ramadhan di Tembilahan - Zariah, Siti; Napratilora, Martina; Nur, Syamsiah; Yudhyarta, Deddy Yusuf; Siagian, Seri Yanti (Universitas Pahlawan Tuanku Tambusai, 2025)
This program aimed to provide Islamic entrepreneurship experience for PAI students through the Ramadhan Stall in Tembilahan. Using practice-based learning, 35 sixth-semester students were divided into seven groups, each receiving IDR 200,000 as initial capital to operate for 20 days. Results showed an increase in understanding of Islamic entrepreneurship concepts from 61.5% to 87.8%, with an average ROI of 22.1%. The implementation of Islamic values reached 90.8%, particularly amanah (94%). Consumer satisfaction was also high (93.6%). This program provided academic, social, and economic benefits, supporting the SDGs, especially Goal 8 (Decent Work) and Goal 4 (Quality Education).